'We've got a file on you': problematising families in poverty in four periods of austerity. (1st June 2020) - Horsley, Nicola; Gillies, Val; Edwards, Rosalind
Abstract : This article considers a genealogy of the governing by data of families in poverty; a case study of the codification of disadvantaged families and problematisation of their difficulties over the course of a century and a half. Influenced by Bacchi's 'what the problem is represented to be' approach, we explore a genealogy of the micro acts of ruling that reveal the practice of constructing and governing of disadvantaged families. We draw on a case study analysis of materials recorded and collected by the Charity Organisation Society and its subsequent guises, during four major periods of recession in Britain, from the late 19th century to the early 21st century. We outline the 'problematisation' approach to governance that underpins our discussion before describing the administrative records with which we worked. We argue that the genealogy of the construction, positioning and governance of poor families over time in this case may be observed in terms of three key shifts in problematisation: (i) from the identification of deservingness towards the assessment of risk; (ii) from a gendered concentration of parents to the perceived needs of children; and (iii) from consultation of authority figures to a reliance on increasingly 'professionalised' data capture tools.